Impact of nuclear dynamics on interatomic Coulombic decay in a He dimer - Sisourat, Nicolas; Kryzhevoi, Nikolai V.; Kolorenč, Přemysl; Scheit, Simona; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
After simultaneous ionization and excitation of one helium atom within the giant weakly bound helium dimer, the excited ion can relax via interatomic Coulombic decay (ICD) and the excess energy is transferred to ionize the neighboring helium atom. We showed [Sisourat et al. Nature Phys. 6, 508 (2010)] that the distributions of the kinetic energy released by the two ions reflect the nodal structures of the ICD-involved vibrational wave functions. We also demonstrated that energy transfer via ICD between the two helium atoms can take place over more than 14 Å. We report here a more detailed analysis of the ICD process and of the impact of the nuclear dynamics on the electronic decay. Nonadiabatic effects during the ICD process and the accuracy of the potential energy curve of helium dimer and of the computed decay rates are also investigated.